Total Quality Management of Sekolah Ramah Anak (SRA) at SDN Ngupasan and SDN Tegalrejo 2, Yogyakarta City - Winur Purbo Sejati; Setya Raharja (Journal of General Education and Humanities, 2026)
This study aims to describe the implementation of Total Quality Management (TQM) in Sekolah Ramah Anak (SRA), a national child-friendly school program in Indonesia, identifying supporting and inhibiting factors at SDN Ngupasan and SDN Tegalrejo 2 in Yogyakarta City. The study used a qualitative approach with a multiple-case design. The research subjects included the principal, the school committee, and students. Data were collected through observation, in-depth interviews, and documentation studies. Data analysis in this study used the Miles and Huberman model, which includes data reduction, data presentation, conclusion drawing, and verification. Data validity was verified through triangulation. The results showed that TQM has been implemented effectively through the principle of customer focus by accepting student and parent input, developing programs based on student interests and talents, involving all school members and related parties, and measuring quality through assessments, parent satisfaction surveys, and academic and non-academic achievement standards. The school's commitment is reflected in its vision, mission, short-term, medium-term, and long-term goals, as well as in continuous improvement based on measurement results. Supporting factors include active participation of the school community, cooperation between parents and related parties, the availability of child-friendly facilities and infrastructure, government support, funding, and training. Inhibiting factors include limited conceptual understanding, suboptimal parental support, limited facilities and funding, minimal training, resistance to change, bullying, and suboptimal data utilization. This research emphasizes the importance of TQM in creating SRA that are safe and comfortable for students.